Impact of Deductible Health Plans on Parental Decision Making for Common Pediatric Otolaryngology Procedures. (October 2018) - Sjogren, Phayvanh P.; Hall, Daniel; Padia, Reema; Stoddard, Gregory J.; Meier, Jeremy D.
Objective: To describe how deductible health plans affect parental decision making for common pediatric otolaryngology operations. Study Design: A cross-sectional survey study. Setting: Tertiary care pediatric hospital. Subjects and Methods: Caregivers of patients aged <18 years were surveyed to assess factors in decision making related to common otolaryngologic surgical procedures, including outpatient tympanostomy tubes and adenotonsillectomy, between July 2015 and June 2016. Children in foster care and those who underwent nonelective surgery were excluded. Decision-making factors were statistically analyzed with univariate and multivariate ordinal logistic regression. Results: A total of 155 caregivers completed the survey. The median age of the patient at the time of the surgery was 3 years. Surgical procedures included tympanostomy tube placement (51%), adenotonsillectomy (37%), tympanostomy tube placement with adenotonsillectomy (10%), and other (2%). The mean ± SD annual deductible per child was $1870 ± $140, and the mean maximum out-of-pocket expense was $3833 ± $235. The odds of having the deductible or out-of-pocket expense affect surgical decision making was greater for those covered under a high-deductible health plan (odds ratio = 2.27; 95% CI, 1.25-4.12; P = .007). Conclusion: High-deductible health plans and out-of-pocket expenses can influence parental decision making for common otolaryngology operations, such as tympanostomy tube placement and adenotonsillectomy. Future studies are needed to determine if such policies affect access to care in the pediatric population.